I. Total synthesis of [plus or minus] ovalicin and its analogues II. Bio-based polymers from vegetable oil III. New synthetic methods of diacetylene fatty acids - Zhao, Huiping (Kansas State University, 2008)
I. Ovalicin is a natural product isolated from the culture of fungus Pseudorotium ovalis Stolk, it selectively inhibit type 2 methionine amino-peptidase (MetAP 2), which related to many physiological activities such as angiogenesis. Total synthesis of [plus or minus] ovalicin, its C4(S*), C4(S*)C5(S*) stereo-isomers, and C5 regio-isomer were synthesized via an intramolecular Heck reaction of (Z)-3-(t-butyldimethyl silyloxy)-1-iodo-1,6-heptadiene utilizing a catalytic amount of palladium acetate. Subsequent epoxidation, dihydroxylation, methylation (or stereochemistry inversion before or after methylation) and oxidation led to a variety of ketones, key intermediates for synthesis of ovalicin and its analogues. Introduction of side-chain to ketones by lithium (Z)-6-methylhepta-2,5-dien-2-ide and following functional group transformation led to ovalicin and its analogues. Anti-trypanosomal activities of various ovalicin analogues and synthetic intermediates were evaluated. II. Bio-based polymers from vegetable oils are renewable and environment-friendly materials. Dihydroxylated, trihydroxylate, tetrahydroxylated and hexahydroxylated triglycerides, triamino and triisopropylamino glycerides were synthesized from model triglyceride glyceryl trioleoate. These monomers were cross-linked with 1, 4-phenylene diisocynate to make polyurethanes and polyureas. The physical properties of these polymers were examined by gel content and swelling value measurements, thermodynamic and viscoelastic properties were studied from TGA, DSC and DMA measurements. The structure-property relationship was discussed based on these measurements. III. Diacetylenic fatty acids were widely applied in material science to regulate alignment on surface and stabilize self-assembled nanomaterials. A novel synthetic method of diacetylenic fatty acids from vegetable oils was developed. Its self-assembling properties on alumina surface were measured and discussed.
Keywords: Total synthesis of Ovalicin; Anti-parasitic activity; Bio-based polymer; Vegetable oil; Synthesis of diacetylene; Self-assembly; Chemistry, Organic (0490); Chemistry, Polymer (0495)